1992
DOI: 10.1021/ma00033a030
|View full text |Cite
|
Sign up to set email alerts
|

Unusual phase behavior of some poly(dialkoxyphosphazenes)

Abstract: An unusual transition from the mesomorphic state to the amorphous state has been found on cooling some poly(dialkoxyphosphazenes). This transition is proved by data obtained from thermomechanical analysis and optical and X-ray investigations. A generalized phase diagram is constructed for these polymers showing the influence of the alkoxy side group length on their glass transition temperatures, crystallization, and ability to form mesophases. The competition of interactions of the polar inorganic main chains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 3 publications
1
32
0
Order By: Relevance
“…144-150°C (<0,1 mm) ' ). I3C NMR (63 MHz): 6 = l19,51 (C4 '),26,[15][16][17][18][19][20][21][22][23][24][25][26]13,25,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]72 (C2,C3),20,31,19,54 (CT,C3'),15,55 (Cl,Cl'),13,68 (C4). a) Distillation of the apolar fraction yielded 12,7 g (60,9%) hexabutylcyclotrisiloxane (purity 99,7% GLC); b.p.…”
Section: Pentabutyl(3-cyanopropyl)cyclotrisiloxane (1) 12)mentioning
confidence: 99%
“…144-150°C (<0,1 mm) ' ). I3C NMR (63 MHz): 6 = l19,51 (C4 '),26,[15][16][17][18][19][20][21][22][23][24][25][26]13,25,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]72 (C2,C3),20,31,19,54 (CT,C3'),15,55 (Cl,Cl'),13,68 (C4). a) Distillation of the apolar fraction yielded 12,7 g (60,9%) hexabutylcyclotrisiloxane (purity 99,7% GLC); b.p.…”
Section: Pentabutyl(3-cyanopropyl)cyclotrisiloxane (1) 12)mentioning
confidence: 99%
“…In this respect, MJLCPs are similar to flexible polymer poly(dialkylsiloxanes) and poly-(di-n-alkoxyphosphazenes) exhibiting a mesomorphic state with no mesogens. [8][9][10][11] The LC phase structures of MJLCPs are identified as columnar nematic phase, 12 hexagonal columnar nematic phase, 13 and hexagonal columnar LC phase 6,7 in which each cylinder is formed by a single MJLCPs chain molecule. 13 Recently, we have observed that the LC phase of some MJLCPs does not appear immediately above glass transition, and the intensity of WAXD decreased on the cooling.…”
Section: Introductionmentioning
confidence: 99%
“…[1,11] Moreover, investigations of the temperature dependence of the intrinsic viscosity [g] were carried out to clear up the role of long-range interactions in PPhPh macromolecules. It was shown experimentally [3,6] that, using such an analysis, additional information could be obtained about the influence of short-and long-range interactions on the macromolecular conformation. For real polymer solutions, according to the Flory equation,…”
Section: Resultsmentioning
confidence: 99%
“…The FB method is used for the determination of the value Dn of solution flow birefringence, which is directly related to the optical anisotropy of the macromolecule, being characterized by the difference (a 1 -a 2 ) between the macromolecular polarizabilities along the backbone (a 1 ) and perpendicular to it (a 2 ). The details of the FB investigation in PPhPh solutions have been described earlier, [4,6,8] and the results obtained are summarized in Table 1 and 2. The macroscopic value characterizing FB is the optical shear coefficient which is equal to…”
Section: Optical Properties Derived From Flow Birefringence Datamentioning
confidence: 99%
See 1 more Smart Citation